2019
DOI: 10.4314/ijs.v21i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectral characterization, and biological activities of Cobalt(II) complexes of Schiff bases derived from <i>o</i>-vanillin and <i>p</i>-vanillin with 3-aminopyridine

Abstract: Highlights • Two 3-aminopyridine derived Schiff bases were synthesized. • Six cobalt (II) complexes of the Schiff bases were synthesized. • The Schiff bases and the cobalt (II) complexes were characterized. • Antimicrobial and brine shrimps activities of the complexes and the Schiff bases were examined Two biologically active Schiff base GL1 and GL2 were synthesized in equimolar reaction of 3-aminopyridine with o-vanillin and p-vanillin. The synthesized Schiff bases were reacted with cobalt acetate, cobalt chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[ 60,61 ] Our compounds manifested a lower degree of toxicity, as evidenced by the small lethality observed only at first (50 μM) or sometimes second (5 μM) concentration level compared to Islam et al [ 60 ] cytotoxic compounds (LC 50 varying between 32.5 μg/ml). Shaibu et al [ 61 ] reported that complexation of ligand to the central metallic ion decreased the toxicity effect on brine shrimp for a number of complexes.…”
Section: Resultsmentioning
confidence: 78%
“…[ 60,61 ] Our compounds manifested a lower degree of toxicity, as evidenced by the small lethality observed only at first (50 μM) or sometimes second (5 μM) concentration level compared to Islam et al [ 60 ] cytotoxic compounds (LC 50 varying between 32.5 μg/ml). Shaibu et al [ 61 ] reported that complexation of ligand to the central metallic ion decreased the toxicity effect on brine shrimp for a number of complexes.…”
Section: Resultsmentioning
confidence: 78%
“…nauplii gut has noticeable changes as observed by a phase-contrast microscope, as shown in Figure . The results suggested that complex 1 accumulation does not induce mortality after 24 h of exposure. …”
Section: Resultsmentioning
confidence: 95%
“…The results suggested that complex 1 accumulation does not induce mortality after 24 h of exposure. 48 50 …”
Section: Resultsmentioning
confidence: 99%
“…Various bands are grouped into the range between 210-245nm, 280-290nm, 302372nm, and 421nm. The first and second band is due to the π to π* transition of benzene & the band above 400nm displayed by Schiff base is attributed to imino n→π* 6,7 The keto-enol tautomer of Schiff base is implied by the presence of these bands in methanol. The transition of these complexes shifted to a higher wavelength.…”
Section: Electronic Spectramentioning
confidence: 98%
“…Azomethine moiety forms complexes with a diversity of metals 4,5 . Many Cu (II) complexes have seemed in the literature with various biological activities 6,7 . The presence of a heterocyclic ring in the Schiff base moiety leads to adding stability to the structure of Schiff base metal complexes 8 .…”
Section: Introductionmentioning
confidence: 99%